2019
DOI: 10.5539/gjhs.v11n13p34
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Access, Utilization, and Level of Satisfaction With Primary Health Care Services in Hafar Al-batain City of Saudi Arabia

Abstract: BACKGROUND: Primary Health Care (PHC) Services in Saudi Arabia has reportedly been poorly accessed and utilized. Another concern is that the kingdom has to be strategic in reducing inequalities that exist between rural and urban communities. At present, there were limited scientific studies on access, utilization, and satisfaction of PHC services in areas most central to the kingdom. AIM: The aim of this study is to explore the factors associated with access, utilization, and level of satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…50 The density of health workers in PHC centers differs across urban and rural areas with the number of physicians being 1766 per ten thousands population in rural areas and 3049 per ten thousands population in urban areas. 50 The inaccessibility of the location of some of the PHCs was stated as a hindrance to receiving services 37 and geography seemed to play a part in this as patients residing in urban areas were generally satisfaction in terms of their accessing and using the PHCs. On the other hand, this was quite the opposite for rural citizens who often cited the length of time it took them to get to these facilities as reasons for their dissatisfaction.…”
Section: Patients' Perceptions Of Phc In Ksamentioning
confidence: 99%
“…50 The density of health workers in PHC centers differs across urban and rural areas with the number of physicians being 1766 per ten thousands population in rural areas and 3049 per ten thousands population in urban areas. 50 The inaccessibility of the location of some of the PHCs was stated as a hindrance to receiving services 37 and geography seemed to play a part in this as patients residing in urban areas were generally satisfaction in terms of their accessing and using the PHCs. On the other hand, this was quite the opposite for rural citizens who often cited the length of time it took them to get to these facilities as reasons for their dissatisfaction.…”
Section: Patients' Perceptions Of Phc In Ksamentioning
confidence: 99%
“…Several studies conducted in Saudi Arabia have revealed that there exist impediments to accessing healthcare services at PHCs. These barriers include a shortage of essential facilities and infrastructure, as well as an insufficient number of healthcare professionals [7,2]. Additionally, the excessive number of patients in PHCs led to extended waiting periods and reduced physician-patient interaction [8].…”
Section: Introductionmentioning
confidence: 99%